2001
DOI: 10.1038/88084
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of proteins by exon shuffling

Abstract: Evolution of eukaryotes is mediated by sexual recombination of parental genomes. Crossovers occur in random, but homologous, positions at a frequency that depends on DNA length. As exons occupy only 1% of the human genome and introns about 24%, by far most of the crossovers occur between exons, rather than inside. The natural process of creating new combinations of exons by intronic recombination is called exon shuffling. Our group is developing in vitro formats for exon shuffling and applying these to the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(141 citation statements)
references
References 81 publications
2
135
0
2
Order By: Relevance
“…In contrast, the gene structure appeared to be more variable in subfamilies II and V, which had the largest number of exon/intron structure variants with striking distinctions. Interestingly, although the exon/intron organization of NACs varied significantly in terms of intron number, the intron phase was remarkably high conserved (Additional file 6), which was indicative of exon shuffling during the evolution process [78]. …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the gene structure appeared to be more variable in subfamilies II and V, which had the largest number of exon/intron structure variants with striking distinctions. Interestingly, although the exon/intron organization of NACs varied significantly in terms of intron number, the intron phase was remarkably high conserved (Additional file 6), which was indicative of exon shuffling during the evolution process [78]. …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the "exon shuffling hypothesis" proposed by Gilbert views the evolution of genes as the recombination of independent units (exons) that code for independent protein structures. Numerous genes have been found where exons do indeed correspond to independent protein domains, and exon shuffling is likely to have played a vital role in the emergence of complex genes and other existing phenomena such as multi-cellularity (Patthy 2003;Kolkman and Stemmer 2001). This concept is evident in our ESGA algorithm that attempts to exploit the intrinsic structure of the BPP by means of an encoding that consists of well-defined sub-solutions that may be recombined in different ways to yield complete optimal solutions.…”
Section: Exon Shufflingmentioning
confidence: 99%
“…This theory has been supported by many studies (Stone et al, 1985;Courseaux & Nahon, 2001;Kolkman & Stemmer, 2001;Long, 2001). It has been suggested that the intron/exon structure of a gene corresponds to its evolutionary history (Duester et al, 1986;Hartung et al, 2002).…”
Section: Discussionmentioning
confidence: 81%
“…Soon after the discovery of split genes, a theory of introndependent evolution was proposed; that introns may participate in the evolutionary process of primordial genes through the shuffling of exonic sequences and that new genes were produced in this way (Gilbert, 1985;Kolkman & Stemmer, 2001). This theory has been supported by many studies (Stone et al, 1985;Courseaux & Nahon, 2001;Kolkman & Stemmer, 2001;Long, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation